(untitled) (Bangladesh Journal of Zoology, 2021)
An observation was made to taste the toxic effect of Vitex negundo L. and Polygonum hydropiper L. (leaf and bark) plants extracts treated fish fed group on rats, Bandicota indica. Six group of rats were fed on two different kinds of plants extracts, one is radiation dose and another untreated control group. These were, the untreated control group rats were feed on normal food such as dried fish and wheat whereas treated rats were given plant extracts and radiation dose treated by dried fish. The experimental rats were fed of 4 ml dose of plant extracts in 70% ethyl alcohol (ratio 1:10) and 4 kGy radiation treated dry fish. The toxic properties of these plant extracts were carried out the vital organs of liver, kidney, stomach, spleens, lungs and muscles on male rats .The lower mammalian species rats were used for preliminary survey their body weight gained and histopathological changes were observed. The experiment was carried out from August 2004 to December 2004. Initially the concentration of rats body weights were found as, control group (C) 43 g/m, Vitex negundo leaf treated fish fed group of rat (VL) 44.8 g/m, Vitex negundo bark treated fish fed group of rat (VB) 44.4 g/m, Polygonum hydropiper leaf treated fish fed group of rat (PL) 46.2 g/m, Polygonum hydropiper bark treated fish fed group of rat (PB) 47.8 g/m and radiation treated fish fed group of rat (R) 47 g/m. After 30 days the weight gain of rats recorded as, group (C) 324.6 g/m, (VL) 357.2 g/m, (VB) 362 g/m, (PL) 342 g/m, (PB) 323.6 g/m and (R) 352 g/m and 90 days after the body weight were group (C) 727.2 g/m, (VL) 781.2 g/m, (VB) 795.8 g/m, (PL) 780.4 g/m, (PB)764.8 g/m and R 789.8 g/m respectively. The present study is, the first attempt to use the rats body weight data found well and most suitable 4ml dose of V. negundo bark treated extracts than leaf treated group and 4 kGy radiation group. Histopathological changes of rats organs test liver was well preserved, kidney-the glomeruli, tubules, blood vessel were showed no significant changes, in the stomach-the mucosa, sub mucosa were well, in the spleen-red and white pulp were showed no significant changes, lung-the alveoli was good and in the muscle-the skeletal muscle were remain unaltered. Bangladesh J. Zool. 49(1): 125-135, 2021